2000
DOI: 10.1054/bjoc.1999.0876
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exogenous growth factors on matrix metalloproteinase secretion by human brain tumour cells

Abstract: Matrix metalloproteinases (MMPs) are a growing family of zinc-dependent endopeptidases that are capable of degrading various components of the extracellular matrix. These enzymes have been implicated in a variety of physiological and pathological conditions including embryogenesis and tumour invasion. The synthesis of many MMPs is thought to be regulated by growth factors, cytokines and hormones. In this study, we investigated the effects of five exogenous growth factors known to be expressed by gliomas [epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 24 publications
3
56
0
1
Order By: Relevance
“…Similar to Nodal, MMP-2 has also been implicated in embryogenesis and tumor invasion (Rooprai et al, 2000). In this study, we showed that the ectopic expression of Nodal or activation of Nodal signaling by addition of rNodal increased MMP-2 protein level and cell invasion.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to Nodal, MMP-2 has also been implicated in embryogenesis and tumor invasion (Rooprai et al, 2000). In this study, we showed that the ectopic expression of Nodal or activation of Nodal signaling by addition of rNodal increased MMP-2 protein level and cell invasion.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding the angiogenic effects of VEGF and Ang-1, several studies have evaluated the role of these molecules in the regulation of gelatinases during angiogenesis. In vitro, VEGF increases both expression and release of MMP-2 and MMP-9 (Lamoreaux et al, 1998;Rooprai et al, 2000;Wang and Keiser, 1998). More recently, Ang-1 have been also described to interfere with MMP-2 and MMP-9 expressions (Das et al, 2003;Kim et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, there are only a few reports of MMP-9 upregulation by this growth factor in human aortic smooth muscle cells (75), human brain tumor cells (76), and human myelo-monocytic leukemia cell lines (74). However, there are no reports demonstrating the up-regulation of MMP-9 in T cells by this growth factor.…”
Section: Discussionmentioning
confidence: 99%